1993
DOI: 10.1007/bf02600139
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation decision making in the elderly

Abstract: CPR preferences changed after an educational intervention. An improved understanding of quantitative outcome data appears to influence the desire for CPR and therefore should be included in CPR discussions with older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
4
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 22 publications
2
56
4
2
Order By: Relevance
“…Because prior studies found that older patients who understand the estimates of outcomes aft er CPR more oft en choose to forgo CPR, the present results may substantially aff ect the choices of some patients and family members. 4,5 Th e results may also inform the discussion about whether life-sustaining vs palliative care should be prioritized in hospitalized older adults who survive CPR but have a high burden of comorbid illness.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because prior studies found that older patients who understand the estimates of outcomes aft er CPR more oft en choose to forgo CPR, the present results may substantially aff ect the choices of some patients and family members. 4,5 Th e results may also inform the discussion about whether life-sustaining vs palliative care should be prioritized in hospitalized older adults who survive CPR but have a high burden of comorbid illness.…”
Section: Discussionmentioning
confidence: 94%
“…3 Older patients who understand CPR outcomes are more likely to choose to forgo CPR. [4][5][6] Th erefore, discussions about life-sustaining treatments, including CPR, in the outpatient setting before older patients become acutely ill are important, and patients and family members value shared decision-making. [7][8][9][10][11] Additionally, patients with chronic disease present a unique opportunity for end-of-life discussions because they are more likely to have contact with health-care providers in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Des enquêtes plus circonscrites réali-sées aux Etats-Unis et en Europe ont donné les mêmes résultats. Outre l'âge, d'autres facteurs jouent également un rôle dans la décision en faveur ou non d'une réanimation, tels que la qualité de vie, l'état de santé, l'environnement social, les valeurs personnelles et la conception de l'existence ainsi que la peur d'une future dépendance [2,3].…”
Section: Quand Les Dispositions De Fin De Vie Sont-elles Importantes?unclassified
“…It is clear that the burden of treatment, the likelihood of beneficial treatment outcomes, and the consequences of toxicity are decisive factors in patients' preferences for specific therapeutic regimens [67][68][69][70][71][72][73][74][75][76][77]. Fried et al examined the treatment preferences of seriously ill patients who had limited life expectancies due to cancer, congestive heart failure, or chronic obstructive pulmonary disease [78].…”
Section: Life Prolongation and Symptom Reliefmentioning
confidence: 99%